2018
DOI: 10.2147/dddt.s178519
|View full text |Cite
|
Sign up to set email alerts
|

Gamma linolic acid regulates PHD2 mediated hypoxia and mitochondrial apoptosis in DEN induced Hepatocellular carcinoma

Abstract: IntroductionHepatocellular carcinoma (HCC) is one of the known major health problems across the globe, and is sixth ranked among all cancer, due to its high mortality rate. Polyunsaturated fatty acids (PUFAs) play an important role in the formation of a cell membrane, along with the fluidity of the membrane and proteins. Gamma linolenic acid (GLA) is member of the ω-6 family of PUFAs and converts into the arachidonic acid via a series of elongation and desaturation reactions. The aim of the current investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…The linoleic acid pathway regulates many physiological processes, then, its metabolic pathway is vital for metabolisms in cancer cells. According to the previous studies, defects in this pathway have been observed in HCC patients, therefore, our results con rm the previous ones [43,44]. Besides, pathways involved with chemical carcinogenesis and cell cycle are associated with cancer development.…”
Section: Discussionsupporting
confidence: 91%
“…The linoleic acid pathway regulates many physiological processes, then, its metabolic pathway is vital for metabolisms in cancer cells. According to the previous studies, defects in this pathway have been observed in HCC patients, therefore, our results con rm the previous ones [43,44]. Besides, pathways involved with chemical carcinogenesis and cell cycle are associated with cancer development.…”
Section: Discussionsupporting
confidence: 91%
“…For example, γ linolenic acid has been shown to reduce cell proliferation and promote the generation of ROS and apoptosis in HCC cell lines [25]. Furthermore, it had a chemo-protective effect against diethylnitrosamineinduced HCCs [26]. EPA-and DHA-enriched diet fed mice were shown to be metabolically healthier with lower lipid and fatty acid biosynthesis as well as upregulation of PPARα and lipid catabolism [27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the achievements in surgical resection and chemotherapy for the treatment of gastric cancer, its recurrence rate and metastasis rate are still high, and the median overall survival (OS) time of patients with metastatic disease is still very poor [3,4]. GLA is a promising bioactive molecule that has anticancer ac-tivity in many types of cancer [18,22,26,27], but its biological activity in gastric cancer is poorly understood. It has been reported that regular intake of GLA could reduce inflammation and inhibit the development of cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, extensive studies have confirmed the potential anticancer effect of these fatty acids [18][19][20][21]. For examples, in vivo experiments have shown that GLA exhibits a dose-dependent regulatory effect on an experimental study on hepatocellular carcinoma [22]. Further studies of underlying molecular mechanisms indicated that GLA may exert a chemical protective effect on DEN-induced liver cancer by altering hypoxic microenvironment, mitochondria-mediated death, apoptosis, and anti-inflammatory pathways [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation